Analysis Marketing Mix On Revisit Interest Of Outpatient Patients At Ploso Hospital, Jombang - Yayuk Utami; Agustin Widyowati; Ratna Wardani; Panca Radono (Universitas STRADA Indonesia, 2024)
Outpatient revisit interest is one of the important aspects to maintain the hospital’s existance. This research aims to identify the influence of the marketing mix on outpatient revisit interest at RSUD Ploso Jombang. This study uses a quantitative research type with a cross-sectional approach. The population consists oof new patient at RSUD Ploso Jombang totaling256 patients, with a sample of 73 respondents using purposive sampling technique. The dependent variable (revisit interest) and independent variables include the marketing mix, which encompasses product, price,place,promotion, process,people, and physical evidence. The research instrument is a questionnaire, and the analysis uses logistic regression test. The research results show that there is a significant influence of product (P-value =0.039) with wald results of 4.242, and process (P-Value =0.037) with wald result 4.355 on outpatient revisit interest. However, there is no significant influence of price (P-Value=0.418), place (P-Value=0.756), promotion (P-Value=0.736), people (P-Value 0.793), physical evidence (P-Value=0.786) on outpatient revisit interest. To attract patients to revisit, it is hoped that RSUD Ploso Jombang can optimize the available products and services by optimizing stock management and working with suppliers. Cooperation with suppliers, conducting regular training for medical staff, and implementing a patient feedback system to improve the availability of medicines and suitability of services for patients are also recommended.